1996
DOI: 10.1152/ajplung.1996.270.2.l173
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular glutathione peroxidase in human lung epithelial lining fluid and in lung cells

Abstract: The epithelial cells of the lower respiratory tract are exposed to high levels of inhaled oxygen and other oxidants. We hypothesized that lung cells would secrete the antioxidant enzyme, extracellular glutathione peroxidase (eGPx), into epithelial lining fluid (ELF). To investigate this hypothesis, we used specific immunoprecipitations of GPx enzymes from ELF, specific immunoprecipitations of 75Se metabolically labeled proteins from lung cells in culture, and in situ hybridization, Northern blot, and reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 0 publications
5
71
1
3
Order By: Relevance
“…It has been reported that incubation with extracellular GSH and increasing intracellular GSH levels protect against oxidant stress in alveolar type II cells [7,195]. In addition, extracellular GPx, which has been described recently [196], is secreted into ELF by alveolar epithelial cells and macrophages and may provide further defence against oxidants [196]. Following acute inflammation and oxidative stress, the ELF may become depleted of antioxidants such as GSH, increasing the potential for damage to the underlying epithelial cells.…”
Section: Antioxidant Protective Genesmentioning
confidence: 99%
“…It has been reported that incubation with extracellular GSH and increasing intracellular GSH levels protect against oxidant stress in alveolar type II cells [7,195]. In addition, extracellular GPx, which has been described recently [196], is secreted into ELF by alveolar epithelial cells and macrophages and may provide further defence against oxidants [196]. Following acute inflammation and oxidative stress, the ELF may become depleted of antioxidants such as GSH, increasing the potential for damage to the underlying epithelial cells.…”
Section: Antioxidant Protective Genesmentioning
confidence: 99%
“…eGPX is one of at least four genetically distinct forms of the antioxidant GPx enzyme family and is found in plasma and respiratory tract lining fluid (12,13). Under oxidative stress conditions, such as during smoking, the eGPX concentrations in the lung increase, in what is believed to be a protective response (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…42 Primary bronchial epithelial cells, alveolar macrophages and other lung cell lines can synthesize classical Gpx and extracellular Gpx and also secrete the extracellular enzyme. 56 Classical Gpx is induced by hyperoxia 57 and by the combination of hyperoxia and TNF. 58 The levels of both classical Gpx and extracellular Gpx are decreased after exposure to ozone.…”
Section: Gpxs In Normal Physiology and Lung Diseasesmentioning
confidence: 99%